FEATURES OF FITNESS MANAGEMENT IN SPORTS AND HEALTH CLUBS - Inozemtseva, E.S.; Zemlyakova, Z.S.; Smertina, A.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify the structure and features of the fitness management of sports and health clubs in the city of Tomsk. Methods and structure of the study. In order to identify the criteria for fitness management of sports and health clubs in the city of Tomsk, a survey was conducted. 115 women took part in the survey. To determine the features of fitness management, taking into account the identified criteria, pedagogical observations of the organization of work and a comparative analysis of the fitness management of sports and health clubs in the city of Tomsk - Freestyle, Super Gym, Dynamite and Manila were carried out. Results and conclusions. Based on the results of the survey, such fitness management criteria as pricing policy, activity in social networks, staff training, brand and recognition were identified. It is shown that when developing a fitness management strategy, it is necessary to correctly calculate the cost of an annual and monthly subscription, regularly introduce discounts, promotions and bonus programs. Those involved in fitness are attracted by additional services on the territory of the club: the presence of a bath, sauna, solarium, children’s room. Events on the territory of the sports and health club significantly increase the recognition of the club.